STRATIFIKASI SOSIAL DAN AKSES TERHADAP PENDIDIKAN ISLAM BERKUALITAS: STUDI DALAM KONTEKS INDONESIA KONTEMPORER - Muchlis Anshori (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2024)
Social stratification in contemporary Indonesian society has significantly influenced the distribution of access to education, including Islamic education, which ideally should be inclusive and equitable. Differences in economic, social, and cultural backgrounds lead to disparities in both access and the quality of education received by students. This study aims to analyze the impact of social stratification on access to quality Islamic education, identify key factors contributing to inequality, and propose a conceptual model for more inclusive Islamic education. This research employs a qualitative approach using a systematic literature review, drawing on reputable academic journals, scholarly books, and recent education policy reports. Data analysis was conducted through literature selection, thematic categorization, interpretation, and conceptual synthesis. The findings indicate that social stratification plays a significant role in shaping access to and quality of Islamic education. Inequality occurs not only at the level of access but also in institutional quality and learning experiences. Furthermore, education policies and digitalization exhibit ambivalent effects, potentially either reducing or reinforcing disparities. Therefore, an integrative model of Islamic education that combines access, quality, and Islamic values is necessary to establish a more inclusive and equitable education system.